A Walk Through the Maze of Secondary Metabolism in Orchids: A Transcriptomic Approach - Ghai, Devina; Kaur, Arshpreet; Kahlon, Parvinderdeep S.; Pawar, Sandip V.; Sembi, Jaspreet K. (Frontiers in Plant Science, 2022)
Orchids have a huge reservoir of secondary metabolites making these plants of immense therapeutic importance. Their potential as curatives has been realized since times immemorial and are extensively studied for their medicinal properties. Secondary metabolism is under stringent genetic control in plants and several molecular factors are involved in regulating the production of the metabolites. However, due to the complex molecular networks, a complete understanding of the specific molecular cues is lacking. High throughput omics technologies have the potential to fill up this lacuna. The present study deals with comparative analysis of high throughput transcript data involving gene identification, functional annotation and differential expression in more than 30 orchid transcriptome datasets, with a focus to elucidate the role of various factors in alkaloid and flavonoid biosynthesis. Comprehensive analysis of the mevalonate (MVA) pathway, methyl-D-erythritol 4-phosphate (MEP) pathway and phenylpropanoid pathway provide specific insights to the potential gene targets for drug discovery. It is envisaged that a positive stimulation of these pathways through regulation of pivotal genes and alteration of specific gene expression, could facilitate the production of secondary metabolites and enable efficient tapping of the therapeutic potential of orchids. This further would lay the foundation for developing strategies for genetic and epigenetic improvement of these plants for development of therapeutic products.